Five new species of the Cnemaspis beddomei clade (Squamata: Gekkonidae) from high elevation, evergreen forests of the Southern Western Ghats, India - Khandekar, Akshay; Thackeray, Tejas; Agarwal, Ishan (Zootaxa, 2024)
We describe five new species allied to Cnemaspis beddomei from the Southern Western Ghats, Tamil Nadu, India using morphological data and mitochondrial sequence divergence. The new species are members of the beddomei and anamudiensis subclades within the beddomei clade and are from boulder habitats in evergreen forests in Tenkasi (Cnemaspis tenkasiensis sp. nov.), and the Agamalai (C. agamalaiensis sp. nov.), Anaimalai (C. anaimalaiensis sp. nov. and C. valparaiensis sp. nov.) and Palani Hills (C. anuradhae sp. nov.). The new species can be distinguished from other members of the beddomei clade and each other by a combination of non-overlapping morphological characters including body size, distinct colouration in males, the number or arrangement of dorsal tubercles around the body and paravertebral tubercles, the number of ventral scales across midbody and longitudinal scales from mental to cloaca, tail tuberculation and arrangement of subcaudal scales, besides uncorrected pairwise ND2 and 16S sequence divergence of ≥ 5.4 % and ≥ 2.3 %. The beddomei clade is another example of extreme micro-endemism, all 23 known species are evergreen forest dwellers and are each known from just one or a few closely spaced localities, with three non-sister species known from within one kilometre straight-line distance of each other on the Valparai Plateau, Anaimalai Tiger Reserve. The beddomei subclade is distributed from Agasthyamalai to the Anaimalais while the anamudiensis subclade is restricted to the Anaimalai, Palani and Kannan Devan Hills.